The impact of context and model choice on the determinants of strategic alliance formation: Evidence from a staged replication study - Ghosh, Anindya; Ranganathan, Ram; Rosenkopf, Lori (Strategic Management Journal, 2016)
Research summary : Endogenous characteristics of alliance network structure have repeatedly been shown to predict future alliance ties in the strategic management literature. Specifically, the concepts and measures of relational, structural, and positional embeddedness (per Gulati and Gargiulo, 1999), as well as interdependence, are foundational for many studies. We explore these determinants of alliance formation by replicating the baseline analyses of Ahuja, Polidoro, and Mitchell's, 2009 SMJ article. We examine the impact of empirical choices with respect to time period, underlying data generating model, and industry by isolating each effect in turn. We demonstrate that while geographic similarity and product‐market similarity each robustly predict the interdependence effect, the effects of both technological similarity as well as the embeddedness predictors are sensitive to context and/or method. Managerial summary : Our examination of alliance formation in the chemical and semiconductor industries during the 1990s demonstrates how new alliances may be predicted by both the technical, geographic, and product‐market fit of potential partners as well as characteristics of each partner's previous network participation. Comparing our results to an earlier study, we find that geographic and product‐market similarity predict alliance formation across both industries and time frames while prior ties between partners predict alliance formation only when these industries are less mature. Other network participation indicators generate nuanced effects, which underscore the importance of quasi‐replications of alliance formation across industries and time periods in building evidence‐based management theories . Copyright © 2016 John Wiley & Sons, Ltd.